Iron deficiency in the Australian high-performance environment: How improved access to iron infusions is enhancing our management - McNamara, A.; McLeod, A.; White, S. (Journal of Science and Medicine in Sport, 2024)
Introduction: Iron deficiency in athletes is common and has a negative effect on performance and health. Ferritin can be difficult to increment in athletes with high training loads; impaired absorption through hepcidin response to exercise or concurrent medical conditions. Repletion of low iron stores is important for the prevention of anaemia, improvement in energy levels for training, and athlete and coach confidence. Medical management of iron deficiency at the Victorian Institute of Sport (VIS) is guided by Sport and Exercise Physicians using the AIS Iron Deficiency Best Practice Guidelines (AIS guidelines). Our increased access to iron infusions has increased uptake and impacted treatment pathways. Methods: Iron management recorded on AMS was retrospectively reviewed between 1/01/2022 and 1/05/2024. VIS athletes are tested for iron stores based on clinical presentation or risk profile for low ferritin or Iron Deficiency Anaemia (IDA). All athletes with low ferritin have dietician involvement, and are advised on oral iron supplementation, including all with a ferritin <35 as per guidelines. Iron infusions are considered for those in AIS Stage 3 IDA, those who inadequately respond to, or are intolerant of oral iron supplements or who require rapid repletion of ferritin for competition or altitude training. Athletes were counselled on infusion risks and provided consent. VIS iron infusion protocol adheres to WADA limits of <100mL injected volume in 12 hours, removing the need for a TUE. Infusions are supervised by a doctor and nurse. Athletes are invited to complete an iron infusion survey at 0 and 3 months and repeat iron studies at 3 months. Referrals to other specialists are made if there is a need to further investigate medical causes of low iron. Results: Of the 441 VIS athletes on scholarship, 305 were serially tested and 1024 ferritin samples were registered. Iron infusion was selected as the most appropriate management on 66 occasions for 57 individual athletes. All infusions were for female athletes, except one. 62% of infused athletes were aged between 18-26, with a further 12% under 18. 48 infusions were completed at the VIS, 9 in a hospital setting often in association with gastroscopy, and 6 externally at medical clinics. Median ferritin prior to infusion was 15, with two thirds <20. The reason for infusion was predominantly due to lack of efficacy of oral supplements (45 athletes) or unacceptable side effects (16 athletes). 8 had upcoming travel and competition. 9 athletes were anaemic (Hb <120 for females) prior to infusion, with just 2 attributable to iron deficiency alone. 12 were referred to gastroenterology for diagnoses including coeliac disease and IBD. Several were managed for heavy menstrual bleeding. Discussion: This presentation will discuss the current application of the AIS iron deficiency guidelines in the high-performance environment at a National Institute Network (VIS). The food-first approach can improve nutrition practices and concurrent low energy availability. Oral iron supplementation continues to be sufficient in many. Our increased access to iron infusions has enhanced our iron management. Impact/Application to the field: Selection of athlete for iron infusion continues to be medically lead at VIS as it often drives investigation for medical causes of low iron. We have observed it to have a favorable side effect profile and efficacy for rapid repletion of ferritin. Declaration: My co-authors and I acknowledge that we have no conflict of interest of relevance to the submission of this abstract.